Clinical Remission of Asthma and Allergic Rhinitis - in a Longitudinal Population Study - Heldin J; Malinovschi A; Johannessen A; Alving K; Holm M; Franklin KA; Forsberg B; Schlünssen V; Jögi R; Gislason T; Benediktsdottir B; Svanes C; et al. (Journal of Asthma and Allergy, 2022)
Johanna Heldin,1 Andrei Malinovschi,2 Ane Johannessen,3 Kjell Alving,4 Mathias Holm,5 Karl A Franklin,6 Bertil Forsberg,7 Vivi Schlünssen,8,9 Rain Jögi,10 Thorarinn Gislason,11,12 Bryndis Benediktsdottir,11,12 Cecilie Svanes,3,13 Christer Janson1 1Department of Medical Sciences: Respiratory, Allergy and Sleep Research, Uppsala University, Uppsala, Sweden; 2Department of Medical Sciences: Clinical Physiology, Uppsala University, Uppsala, Sweden; 3Centre for International Health, Department of Global Public Health and Primary Care, University of Bergen, Bergen, Norway; 4Department of Women’s and Children’s Health, Paediatric Research, Uppsala University, Uppsala, Sweden; 5Occupational and Environmental Medicine, School of Public Health and Community Medicine, Institute of Medicine, University of Gothenburg, Gothenburg, Sweden; 6Department of Surgical and Perioperative Sciences, Surgery, Umeå University, Umeå, Sweden; 7Department of Public Health and Clinical Medicine, Section of Sustainable Health, Umeå University, Umeå, Sweden; 8Department of Public Health, Unit for Environment, Occupation and Health, Danish Ramazzini Centre, Aarhus University, Aarhus, Denmark; 9National Research Center for the Working Environment, Copenhagen, Denmark; 10Tartu University Hospital, Lung Clinic, Tartu, Estonia; 11The Medical Faculty, University of Iceland, Reykjavik, Iceland; 12Department of Sleep, Landspitali University Hospital Reykjavik, Reykjavik, Iceland; 13Department of Occupational Medicine, Haukeland University Hospital, Bergen, NorwayCorrespondence: Christer Janson, Department of Medical Sciences: Respiratory, Allergy and Sleep Research, Uppsala University, Uppsala, Sweden, Email christer.janson@medsci.uu.seBackground: Although asthma and allergic rhinitis are chronic diseases, some patients experience periods of remission. Information on prognostic factors associated with the remission of asthma and allergic rhinitis is valuable in resource prioritization. This study investigated factors associated with the clinical remission of asthma and allergic rhinitis.Methods: In the Respiratory Health In Northern Europe (RHINE) study, data was collected with questionnaires in stage one (RHINE I, 1989– 1992) and two follow-ups (RHINE II, 1999– 2001 and RHINE III, 2010– 2012) from Sweden, Norway, Denmark, Iceland and Estonia. Clinical remission was defined as having reported asthma or allergic rhinitis in RHINE I or RHINE II but not in RHINE III.Results: Of 13,052 participants, 975 (7.5%) reported asthma in RHINE I or RHINE II, and 3379 (25.9%) allergic rhinitis. Clinical remission of asthma and allergic rhinitis was found in 46.4% and 31.8%, respectively. Living in Estonia (OR (95% CI) 2.44 (1.22– 4.85)) and living in an apartment (1.45 (1.06– 1.98)) were related to remission of asthma, while subjects reporting allergic rhinitis (0.68 (0.51– 0.90)), asthma onset ≤ 12 years of age (0.49 (0.35– 0.68)), receiving treatment with antibiotics for respiratory illness (0.64 (0.47– 0.87)) were less likely to have asthma remission. Factors related to a higher likelihood of remission of allergic rhinitis were no asthma at baseline, age ≥ 58 years in RHINE III, allergic rhinitis onset after 12 years of age, living in rural areas as a child, having only a primary school education and not being pregnant.Conclusion: Clinical remission was found in almost one-half of those with asthma and one-third of persons with allergic rhinitis. Coexisting allergic symptoms were associated with less clinical asthma remission. Age, asthma symptoms and environmental factors in childhood, such as living in a rural area, were found to influence the clinical remission of allergic rhinitis.Keywords: asthma, allergic rhinitis, remission, epidemiology